PENERAPAN MODEL DISCOVERY LEARNING PADA MATERI KEPENDUDUKAN JEPANG DI INDONESIA - Rofida, Wiwit Nurin (JURNAL PENDIDIKAN IPS, 2024)
The form of the nationalist character of class XI students has not been clearly seen, the sense of responsibility as students who have the character of nationalism fade. In reality, the younger generation in the current era is less interested in the history of the nation. In learning history, the dominant teacher uses lecture and discussion methods so that students are bored and passive. One of the efforts to solve this problem is the application of an e-booklet-based discovery learning model in learning history on Japanese population material in Indonesia to foster the nationalist character of class XI students. This research uses descriptive qualitative research. Data collection techniques in this study using observation, interviews and documentation. The results of this study indicate that the application of the discovery learning model based on e-booklets on the Japanese population material in Indonesia class XI at SMAN 1 Tulungagung, namely students can find the idea of essential values contained in the Japanese population material in Indonesia through e-booklet media by applying the discovery learning model in the form of integrity values, patriotism , and love for the homeland as an effort to instill the values of nationalism in students. The implication of the application of the discovery learning model based on e-booklets on Japanese population material in Indonesia class XI at SMAN 1 Tulungagung is that students can apply the value of integrity when learning history, students can apply the value of patriotism when learning history, students can apply the value of love for the homeland in when studying history.